Secondary metabolites of Streptomyces strains AAR1-1 and AAR 14 associated with marine sponges - Chutima Petchprayoon (Chulalongkorn University, 2007)
Thesis (M.Sc. in Pharm.)--Chulalongkorn University, 2000